2008
DOI: 10.1002/dc.20854
|View full text |Cite
|
Sign up to set email alerts
|

Cytological features of myxoid adrenocortical adenoma with a pseudoglandular component: A case report with differential diagnostic considerations

Abstract: Myxoid adrenocortical tumors are extremely rare neoplasms with only nine adenomas and eleven carcinomas reported in the literature. They occasionally have a pseudoglandular component resembling metastatic mucinous adenocarcinoma in the adrenal gland. However the cytological features of this unusual tumor have not been previously described. We report here the first cytopathological study of a myxoid adrenocortical adenoma with a pseudoglandular component, contributing especially to the differential diagnosis fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…In addition, four out of six myxoid ACAs reported in a series by Brown et al [49] were large (≥ 6 cm), showed focal capsular invasion and a mitotic activity of ≥ 1/10 HPFs in the absence of recurrence or metastatic disease after a mean follow-up period of 12 years. It should be stressed that 9 out of 17 myxoid ACAs were relatively large (≥ 6 cm), a feature further challenging the prediction of a benign clinical course [49, 50, 5457]. …”
Section: Part II Adrenocortical Carcinoma Variantsmentioning
confidence: 99%
“…In addition, four out of six myxoid ACAs reported in a series by Brown et al [49] were large (≥ 6 cm), showed focal capsular invasion and a mitotic activity of ≥ 1/10 HPFs in the absence of recurrence or metastatic disease after a mean follow-up period of 12 years. It should be stressed that 9 out of 17 myxoid ACAs were relatively large (≥ 6 cm), a feature further challenging the prediction of a benign clinical course [49, 50, 5457]. …”
Section: Part II Adrenocortical Carcinoma Variantsmentioning
confidence: 99%
“…To date, including adenomas and carcinomas, a total of 41 cases (21 carcinomas, 3 borderline malignancies, and 17 adenomas) have been reported in the English literature. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Because the presence of myxoid changes in adrenocortical neoplasms often raises the possibility of malignancy, we aimed to explore the clinicopathologic and molecular biologic features of myxoid adrenocortical neoplasms in this study.…”
Section: Detection Of Egfr Protein Expression May Be Useful In the DImentioning
confidence: 99%
“…Following the original report by Tang and coworkers (26), 32 functioning or non-functioning myxoid ACT have been described, including 18 adenomas, 13 carcinomas and one borderline case (3,4,6,7,9,10,(13)(14)(15)(16)(17)19,23,25,30). Myxoid changes may also be present in pediatric ACT, judging from the images (Fig.…”
Section: Introductionmentioning
confidence: 99%